Benign gallbladder disease is a risk factor for colorectal cancer, but cholecystectomy is not: A propensity score matching analysis - Qin, Qiong; Li, Wei; Ren, Ao; Luo, Rong; Luo, Shiqiao (Frontiers in Oncology, 2022)
Background: Previous studies reported controversial results on the relationship between cholecystectomy (CHE) and colorectal cancer (CRC). We hypothesized that gallbladder disease (GBD), instead of cholecystectomy, increased the risk of CRC. We aimed to investigate the incidence of benign gallbladder disease (BGBD) and CHE in CRC patients and local adults undergoing annual health examination by analyzing large data from a tertiary hospital in southwest China. Methods: A propensity score matching (PSM) analyzed, retrospective study from January 1, 2013, to August 31, 2020, including 7,471 pathologically confirmed CRC patients and 860,160 local annual health examination adults in the First Affiliated Hospital of Chongqing Medical University, was conducted. The prevalence of BGBD and the CHE rate were analyzed before and after a 1:1 PSM. Results: Of the 7,471 CRC patients, 7,160 were eligible for the case group. In addition, 860,160 local health examination adults were included for comparison. The incidence of BGBD was higher in the CRC patients than in the local adults (19.2% vs. 11.3%, P < 0.001), but no significant difference in CHE rate existed between the case group and the control group (5.0% vs. 4.8%, P = 0.340). In the subgroup analysis, patients with BGBD had a higher risk of colon cancer than rectal cancer (20.4% vs. 18.2%, P = 0.024) and more significantly in the right colon (P = 0.037). A weakly positive correlation between CHE and right colon cancer was observed before PSM but no longer existed after PSM (P = 0.168). Conclusions: Benign gallbladder disease was positively correlated with colorectal cancer, especially right colon cancer. Cholecystectomy did not increase the risk of colorectal cancer.